NAVIGATING DIGITAL LITERACY TO REDUCE CYBERBULLYING IN ADOLESCENTS - Indarto, Mukhamad Diki; Huda, Muhammad; Utomo, Imam Aris; Ramadhan, Ari Maulana; Annur, Fauzi (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2025)
ABSTRACT The rapid advancement of digital technology presents both opportunities and risks for adolescents, one of which is the rising incidence of cyberbullying manifested in forms such as flaming, online harassment, and the dissemination of personal information. This situation affects adolescents’ psychological well-being, physical health, and academic performance, thereby requiring systematic preventive measures. This study aims to examine the role of digital literacy in reducing cyberbullying behavior through a literature review of relevant national and international publications. The selected articles were analyzed using a content analysis approach to identify recurring patterns, key concepts, and effective prevention strategies aligned with the dynamics of adolescents’ digital engagement. The findings indicate that digital literacy not only enhances technical abilities but also strengthens critical thinking skills, ethical awareness, and understanding of privacy protection, all of which directly contribute to reducing aggressive behavior in digital spaces. The review also highlights that school-based digital literacy programs, parental involvement, the use of educational technologies, and regulatory support such as the Electronic Information and Transactions Law (UU ITE) positively influence adolescents’ resilience against online threats. However, challenges such as unequal infrastructure readiness, varying literacy levels, and limited intensive supervision remain obstacles to optimal implementation. Overall, the study concludes that collaboration among educational institutions, families, the government, and digital platform providers serves as a fundamental basis for creating a safe, ethical, and supportive digital ecosystem for adolescent development. ABSTRAK Kemajuan teknologi digital yang berlangsung cepat menghadirkan peluang sekaligus risiko bagi remaja, salah satunya meningkatnya kasus cyberbullying yang muncul dalam bentuk flaming, pelecehan daring, dan penyebaran data pribadi. Situasi ini berdampak pada kondisi psikologis, kesehatan fisik, serta prestasi akademik remaja, sehingga diperlukan langkah pencegahan yang sistematis. Penelitian ini bertujuan mengkaji peran literasi digital dalam menekan perilaku cyberbullying melalui tinjauan pustaka terhadap berbagai publikasi nasional dan internasional yang relevan. Artikel-artikel terpilih dianalisis menggunakan pendekatan analisis isi untuk menelusuri pola temuan, konsep kunci, dan strategi pencegahan yang sesuai dengan dinamika aktivitas digital remaja. Hasil kajian menunjukkan bahwa literasi digital tidak hanya meningkatkan kemampuan teknis, tetapi juga memperkuat kecakapan berpikir kritis, kesadaran etis, dan pemahaman mengenai perlindungan privasi, yang secara langsung berkontribusi mengurangi kecenderungan perilaku agresif di ruang digital. Temuan juga menegaskan bahwa implementasi program literasi digital di sekolah, keterlibatan orang tua, pemanfaatan teknologi edukatif, serta dukungan regulasi seperti UU ITE berpengaruh positif dalam membangun ketahanan remaja terhadap ancaman dunia maya. Adapun hambatan berupa kesenjangan infrastruktur, perbedaan tingkat literasi, dan terbatasnya pendampingan intensif masih menjadi faktor penghambat. Secara keseluruhan, studi ini menyimpulkan bahwa kolaborasi antara institusi pendidikan, keluarga, pemerintah, dan penyedia platform digital merupakan fondasi utama untuk mewujudkan ekosistem digital yang aman, etis, dan mendukung perkembangan remaja.